2016
DOI: 10.1177/0306624x15625991
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Narrative Experience: Relating Emotions to Offence Narrative Roles During Crime Commission

Abstract: A neglected area of research within criminality has been that of the experience of the offence for the offender. The present study investigates the emotions and narrative roles that are experienced by an offender while committing a broad range of crimes and proposes a model of Criminal Narrative Experience (CNE). Hypotheses were derived from the Circumplex of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 61 publications
(101 reference statements)
2
50
0
1
Order By: Relevance
“…One interesting finding in this research emphasised that individuals demonstrated a stronger distinction between pleasure and displeasure in comparison with normal noncriminal experiences (Canter & Ioannou, ). Similarly, further research has replicated the full gamut of Russell's () emotions amongst male offenders highlighting four main affective themes: elation, calm, distress, and depression (Canter & Ioannou, ; Ioannou, ; Ioannou, Canter, & Youngs, ).…”
Section: Emotions and Crimementioning
confidence: 86%
“…One interesting finding in this research emphasised that individuals demonstrated a stronger distinction between pleasure and displeasure in comparison with normal noncriminal experiences (Canter & Ioannou, ). Similarly, further research has replicated the full gamut of Russell's () emotions amongst male offenders highlighting four main affective themes: elation, calm, distress, and depression (Canter & Ioannou, ; Ioannou, ; Ioannou, Canter, & Youngs, ).…”
Section: Emotions and Crimementioning
confidence: 86%
“…Unlike in Ioannou et al's (2016) sample, offenders felt scared, upset and worried, but also courageous for acting. They were looking for some sort of recognition.…”
Section: Depressed Victimmentioning
confidence: 68%
“…To test the hypothesis that emotions and narrative roles would present in distinct regions, the SSA plot was examined. Emotions and narrative roles appear to form four themes previously identified by Ioannou et al (2016) 25what was happening was just fate, (26) it all went to plan, (27) it was a manly thing to do, (28) it was just a usual days work, (29) it was like being on an adventure, (30) it was the only thing I could think of doing, (31) I knew I was taking a risk, (32) I knew it was going to happen.…”
Section: Themes Of Emotions and Narrative Rolesmentioning
confidence: 72%
See 1 more Smart Citation
“…However, it has been reported (Youngs, Ioannou, & Eagles, ) that specialisation is represented through expressive and instrumental offenders, although if this relates to geo‐behaviour remains unclear. It would be useful to examine the criminal narratives of these two groups of offenders as has been successfully applied in other studies (Ioannou, Canter, Youngs, & Synnott, ; Ioannou, Canter, & Youngs, ; Ioannou, Hammond, & Simpson, ; Ioannou, Synnott, Lowe, & Tzani‐Pepelasi, ; Ioannou, Synnott, Reynolds, & Pearson, ; Yaneva, Ioannou, Hammond, & Synnott, ). This would be in respect to their geographic profiles to ascertain if the lack of variation is geographic behaviour is consistent in their offender narrative.…”
Section: Discussionmentioning
confidence: 99%